(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article analyzes the role of tax policy in ensuring business resilience in the face of external economic shocks. A comparative review of national tax regulation models is provided, ranging from temporary anti-crisis measures to long-term incentives for investment in sustainable development. Based on data from international organizations and relevant research, the most effective approaches are identified, as well as the institutional factors that determine their effectiveness.